The Moduli Spaces of Parabolic Connections with a Quadratic Differential and Isomonodromic Deformations - Komyo, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
In this paper, we study the moduli spaces of parabolic connections with a quadratic differential. We endow these moduli spaces with symplectic structures by using the fundamental 2-forms on the moduli spaces of parabolic connections (which are phase spaces of isomonodromic deformation systems). Moreover, we see that the moduli spaces of parabolic connections with a quadratic differential are equipped with structures of twisted cotangent bundles.